Maize grain production, plant nutrient concentration and soil chemical properties in response to different residue levels from two previous crops. (18th May 2020) - Hirzel, Juan; Undurraga, Pablo; León, Lorenzo; Panichini, Marcelo; Carrasco, Jorge; González, Jorge; Matus, Iván
ABSTRACT: The incorporation of previous crop residues in agricultural management benefits soil fertility, crop production, and environment. However, there is no enough information about maximum residue application level without negative effect over next crop yield. To evaluate maize ( Zea mays L.) yield under short-time conservation management with incorporation and/or importation of different residue levels, a biannual rotation experiment was conducted in ash volcanic soil in south-central Chile. The experiment consisted of two previous crops, canola ( Brassica napus L.) and bean ( Phaseolus vulgaris L.), and four levels of residue incorporation (0%, 50%, 100%, and 200% of generated residue; from 0 to 21.4 Mg ha −1 for canola and from 0 to 19.0 Mg ha −1 for bean). Previous crop species and residue level affected some nutrients concentrations in grain and plant and some soil chemical properties, without effect in maize yield, which averaged 16.6 Mg ha −1 . Bean residue increased Ca and reduced S in maize plant, increasing soil P, Ca, Mg and K ( P  < 0.05). Maize grain Ca content was positively and proportionally affected by canola residue level and negatively and proportionally affected by bean residue level. All canola residue levels increased soil pH and Mg, but the highest level reduced soil S; soil P concentration increased proportionally with bean residue level. The highest bean residue level increased soil S. Different crop and levels of residue did not affect maize yield but did some plant nutrient concentration, and also affected some soil chemical properties.